Hashtag activism and the configuration of counterpublics: Dutch animal welfare debates on Twitter. Issue 12 (10th September 2021) - Wonneberger, Anke; Hellsten, Iina R.; Jacobs, Sandra H. J.
ABSTRACT: Social media platforms provide major opportunities for online activism and the emergence of digital counterpublics. Research on counterpublics has focused on actors and their narrative strategies aiming at deconstructing dominant discourses. Less attention has been paid to how the interplay between actors and platform-specific functions affects the configurations and therewith also the success of digital counterpublics. Existing studies mainly rely on determining up front which topics, actor characteristics, or arguments constitute hashtag activism and digital counterpublics. In contrast, our approach allows for an empirical identification based on how actors position themselves in an online debate toward other actors and their shared hashtags. We argue that online activism is co-constituted by actors and their usage of hashtags, actor mentions, and retweets. Applying a communicative network perspective allows for the integration of semantic and relational research traditions. We combine a recently developed automated network analysis method and content analysis to analyze two Twitter debates about animal welfare issues. Our results show that among Twitter users, citizens and environmental organizations formed a common cluster whereas media actors formed their own sub-clusters in both debates. The findings emphasize the central role of citizens for the configuration of digital counterpublics. The proposed approach can be further adapted and applied more widely for the analysis of online activism and debates.